IoT approach for smart cities based on edge computing - Kenioua Laid (Universty Of El-oued جامعة الوادي, 2025)
الملخص: لقد برزت الحوسبة الحافة كتكنولوجيا تحويلية تعمل على معالجة البيانات بالقرب من مصدرها بدلا من الاعتماد على مراكز البيانات المركزية البعيدة أو السحابة, يقلل هذا النهج بشكل كبير من زمن الوصول، ويعزز سرعة المعالجة، ويمكن من اتخاذ القرارات في الوقت الفعلي، مما يجعله مثاليا لتلبية الاحتياجات الديناميكية للمدن الذكية في البيئات الحضرية، تلعب الحوسبة الحافة دورا حاسما من خلال دعم تطبيقات مختلفة مثل إدارة حركة المرور الذكية ومراقبة استهلاك الطاقة والسلامة العامة من خلال الكاميرات وأجهزة الاستشعار الذكية, تساهم الحوسبة الحافة في إنشاء أنظمة حضرية أكثر كفاءة واستجابة واستدامة في الوقت الفعلي من خلال تمكين تحليل البيانات بشكل أسرع وتقليل العبء على الشبكات المركزية، وبالتالي المساهمة في تطوير المدن الذكية, في هذه الاطروحة، تستخدم تقنيات وأساليب الحوسبة الحافة لدعم تطوير وتشغيل المدن الذكية في تطبيقات مختلفة بما في ذلك دعم عمل السيارات ذاتية القيادة وتطبيقات الرعاية الصحية ودعم أمن البيانات في وحدات الحوسبة الحافة, يسمح هذا التكامل بين الحوسبة الحافة والمدن الذكية بجمع البيانات وتحليلها بالقرب من وحدة المعالجة، مما يسمح للتطبيقات باتخاذ القرارات في الوقت الفعلي وتحسين أدائها. Abstract: Edge computing has emerged as a transformative technology that processes data close to its source, rather than relying on remote centralized data centers or the cloud. This approach significantly reduces latency, enhances processing speed, and enables real-time decision-making, making it ideal for meeting the dynamic needs of smart cities. In urban environments, edge computing plays a critical role by supporting various applications such as smart traffic management, energy consumption monitoring, and public safety through smart cameras and sensors. Edge computing contributes to creating more efficient, responsive, and sustainable urban systems in real time, by enabling faster data analysis and reducing the burden on central networks, thus contributing to the development of smart cities. In this thesis, we use edge computing techniques and methods to support the development and operation of smart cities in various applications including supporting the work of self-driving cars, healthcare applications, and supporting data security in edge computing units. This integration between edge computing and smart cities allows data to be collected and analyzed close to the processing unit, allowing applications to make decisions in real time and improve their performance.
Thèse de Doctorat
Keywords: حوسبة الحافة; المدن الذكية; إنترنت الاشياء; البيانات الضخمة; Edge Computing; Smart Cities; IOT; Big Data